Photographic Facial Soft Tissue Analysis by Means of Linear Measurements in Adult Pakistani Population - Anum Aziz, Muhammad Imran Rahbar, Naseer Ahmad Chaudhry, Saadia Ata, Qasim Khalid, Sapna Nadeem (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Achieving pleasant and well balanced face is primary objective of orthodontic management. Comprehending facial tissues and acceptable range of structures, allows formulation of treatment plan. Objectives: This study rationale was to establish mean linear photogrammetry norms for adult Pakistanis, to aid in diagnosis, planning of treatment, esthetics and stability in the therapy results, for local population. Methods: A cross sectional study, on 78 subjects from Fatima Memorial Hospital and undergraduate scholars of Fatima Memorial College of Dentistry. Gathered data was logged and examined in SPSS 20. Quantitative variables were expressed as mean and standard deviation. Categorization ofgender and age was carried out to check distractors and independent t-test was used, with p-value ≤ 0.05 as significant statistically. Result: Result of this research exhibited marked variation in genders for length of lower lip, which was shorter in females than males. The length of lower lip which was significant on the basis of gender, was statistically insignificant on the basis of age. All other parameters showed statistically insignificant difference on the basis of gender and age. Conclusion: This research concluded that average values for gender and age for linear parameters must be used while planning cases for orthodontic therapy ofpatients of Pakistani origin. Keywords: Photogrammetry, Esthetics, Soft Tissue, Orthodontics, Treatment Planning, Diagnosis.